Left ventricular mechanics in late second trimester of healthy pregnancy. (4th September 2019) - Meah, V. L.; Backx, K.; Cockcroft, J. R.; Shave, R. E.; Stöhr, E. J.
ABSTRACT: Objective: To evaluate left ventricular (LV) mechanics in the second trimester of healthy pregnancy and to determine the influence of underpinning hemodynamics (heart rate (HR), preload and afterload) on LV mechanics during gestation. Methods: This was a cross‐sectional study of 18 non‐pregnant, 14 nulliparous pregnant (22–26 weeks' gestation) and 13 primiparous postpartum (12–16 weeks after delivery) women. All pregnant and postpartum women had uncomplicated, singleton gestations. Cardiac structure and function were assessed using echocardiography. LV mechanics, specifically longitudinal strain, circumferential strain and twist/untwist, were measured using speckle‐tracking echocardiography. Differences between groups were identified using ANCOVA, with age, HR, end‐diastolic volume (EDV) and systolic blood pressure (SBP) as covariates. Relationships between LV mechanics and hemodynamics were examined using Pearson's correlation. Results: There were no significant differences in LV structure and traditional measurements of systolic and diastolic function between the three groups. Pregnant women, compared with non‐pregnant ones, had significantly higher resting longitudinal strain (–22 ± 2% vs –17 ± 3%; P  = 0.002) and basal circumferential strain (–23 ± 4% vs –16 ± 2%; P  = 0.001). Apical circumferential strain and LV twist and untwist mechanics were similar between the three groups. No statistically significant relationships were observed between LV mechanics and HR, EDV or SBP within the groups. Conclusions: Compared to the non‐pregnant state, pregnant women in the second trimester of a healthy pregnancy have significantly greater resting systolic function, as assessed by LV longitudinal and circumferential strain. Contrary to previous work, these data show that healthy pregnant women should not exhibit reductions in resting systolic function between 22 and 26 weeks' gestation. The enhanced myocardial contractile function during gestation does not appear to be related to hemodynamic load and could be the result of other physiological adaptations to pregnancy. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.